Analysis and test definition of adhesively bonded joints in aircraft structures - Tiwari, Prashant Anil (My University, 2022)
This report covers the analyses of the adhesively bonded joints in the cargo door of the Clean Sky 2 project FMCD. Adhesives undergo large rotation and its failure is dependent on hydrostatic and deviatoric stresses. Extended Drucker-Prager method has been used to capture the elastoplastic response of the adhesive in FEM. Adhesives and adherends are modelled as hexahedral elements. Spew fillets are used to reduce the effect of singularities at the edge of the joints. To keep the computational time less, only the critical location is modelled with solid adhesive and adherends. 1D elements with adhesive material properties are used to model the non critical regions. The FE method shows promising results at the critical regions where analytical method did not
Keywords: Aircraft; Adhesive; Finite element method; Drucker-Prager